USAGE OF UNMANNED AERIAL VEHICLES IN GENERAL AVIATION: CURRENT SITUATION AND PROSPECTS - V. N. Zhuravlev; P. V. Zhuravlev (Научный вестник МГТУ ГА)
The article aims at analyzing the current and future trends in usage of Unmanned Aerial Vehicles (UAV) in general aviation (branches of economy). The main goal of the analysis is to determine the branches of economy, in which the usage of UAVs would be the most beneficial in the near- to mid-term future. The main requirements and restrictions of usage of the aircraft in general aviation were used as a basis for determining the types of operations, in which the usage of UAVs will be the most rational and effective. The effectiveness evaluation was based on the developed method, involving evaluation of the following factors such as: advantages of usage of manned aircraft, advantages of usage of unmanned aircraft, problems associated with the usage of manned aircraft, problems associated with the usage of unmanned aircraft. After evaluation of the mentioned aspects above the safety, operational productivity and ecological indicators were evaluated. These qualitative assessments allowed identifying the branches of economy, where the usage of UAVs could potentially be the most advantageous. The article also discusses the possible strategies of UAVs development for general aviation. The so-called “mixed” strategy of UAV development is identified as the best in the current situation. This strategy combines the conversion of the existing military UAVs with the purpose of fitting them in to civilian use with the parallel development of brand new UAVs, which would be designed for operation in branches of economy right from the beginning (from scratch).